A gap waveguide-based mechanically reconfigurable phase shifter for high-power Ku-band applications - Farahbakhsh, Ali; Zarifi, Davood; Mrozowski, Michal (Scientific reports, 2024)
This paper presents a novel design of a low-loss, reconfigurable broadband phase shifter based on groove gap waveguide (GGW) technology. The proposed phase shifter consists of a folded GGW and three bends with a few pins forming the GGW and one bend attached to a movable plate. This movable plate allows for adjustments to the folded waveguide length, consequently altering the phase of electromagnetic waves. The advantage of GGW technology is that it does not require electrical contact between different parts of a structure. Therefore, it enables the moving parts to slide freely without electromagnetic energy leakage, resulting in improved insertion loss in high-power applications. In addition, in the proposed design, the position of the input and output waveguide ports of the phase shifter remains fixed, which is advantageous from a practical point of view. As shown by measurement and simulation results, there is nearly 37% impedance bandwidth with the highest insertion loss of 0.6 dB, and the developed device has a maximum phase shift of 770° at the center frequency of 13 GHz. The phase shifter can be used for various radar and satellite applications that require phase control, such as beamforming networks and phased array antennas.